Local analogs of high-redshift galaxies: Metallicity calibrations at high-redshift. Issue Volume 15:Issue S352(2019) (June 2019) - Bian, Fuyan; Kewley, Lisa J.; Groves, Brent; Dopita, Michael A.
Abstract: We study the metallicity calibrations in high-redshift galaxies using a sample of local analogs of high-redshift galaxies selected from the SDSS survey. Located in the same region on the BPT diagram as star-forming galaxies at z ∼ 2, these high-redshift analogs share the same ionized ISM conditions as high-redshift galaxies. We establish empirical metallicity calibrations between the direct gas-phase oxygen abundances and varieties of metallicity indicators in our local analogs using direct T e method. These new metallicity calibrations are the best means to measure the metallicity in high-redshift galaxies. There exist significant offsets between these new high-redshift metallicity calibrations and local calibrations. Such offsets are mainly driven by the evolution of the ionized ISM conditions from high-z to low-z.